Isolation and Identification of Lactic Acid Bacteria form Chinese Cabbage Waste by 16s rRNA Amplification using The Polymerase Chain Reaction (PCR) Method - Junitasari, Assyifa; Rosahdi, Tina Dewi; Lestari, Yuni Siti (Syarif Hidayatullah State Islamic University, 2023)
Waste is material that is disposed of from sources of human and natural activities that do not yet have economic value. Physically, vegetable waste is perishable due to its high-water content, especially Chinese Cabbage waste. The purpose of this study was the isolation and identification of lactic acid bacteria from Chinese Cabbage waste. Isolation was carried out to obtain isolates of lactic acid bacteria from Chinese Cabbage waste. Then it was amplified using a Polymerase Chain Reaction (PCR) instrument. The results of chromosomal DNA amplification of bacterial isolates from mustard 1, mustard 2 and mustard 3 waste showed DNA bands with a size of ± 1200 bp, so it can be concluded that the process of amplification of the 16s rRNA gene fragment in mustard 1, mustard 2 and mustard 3 isolates was successful. The results of the 16s rRNA base sequence analysis showed that the mustard 1 isolate had a similarity index of 84.65% with Bacillus sp, the gene for the mustard 2 isolate had a similarity index of 84.09% with the Uncultured bacterium clone, and the mustard 3 isolate gene had a similarity index of 85.42% with Environmental 16s rDNA sequence.